Three-dimensional ordered aperture-adjustable iron-aluminum composite metal oxygen carrier and preparation and application thereof
The preparation of three-dimensional, orderly and adjustable pore size iron-aluminum composite metal oxygen carrier through impregnation method solves the problem of easy deactivation of existing iron-based oxygen carriers in high temperature environments, and realizes the high oxygen transport capacity and reaction of the oxygen carrier. Active, prolonging its service life.
Patent Information
- Application Number
- CN202411539427.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
Existing iron-based oxygen carriers are prone to decrease oxygen mobility, sintering and agglomeration under high temperature environments, resulting in reduced chemical activity and accelerated inactivation, affecting the efficiency and safety of the biomass chemical chain gasification process.
The iron-aluminum composite metal oxygen carrier with three-dimensional orderly adjustable pore size was prepared by impregnation method. Through impregnation and calcination of polystyrene cement templates and aluminum salt and iron salt precursor solutions, a high specific surface area, developed pore structure and Structural stability of oxygen carrier.
It significantly slows down the agglomeration phenomenon of oxygen carrier, improves oxygen transport capacity and reaction activity, delays the inactivation of oxygen carrier, and enhances its application performance in biomass chemical chain gasification process.
Smart Images

Figure HDA0005112422910000011 
Figure HDA0005112422910000012 
Figure HDA0005112422910000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and specifically relates to a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size, and preparation and application thereof. Background Art
[0002] Biomass energy is a renewable energy source. In the current situation of energy shortage, vigorously developing biomass energy utilization technology is conducive to achieving the dual carbon goals as soon as possible. Currently, biomass pyrolysis technology and biomass gasification technology in biomass utilization technology can convert biomass energy into secondary energy, which can be converted into heat, biochar, bio-oil and synthesis gas. Based on biomass gasification technology and chemical chain combustion technology, scientists have proposed chemical chain gasification technology.
[0003] Chemical chaining gasification technology has attracted much attention due to its advantages of high separation efficiency, carbon separation, and low air cost. The concept of chemical chaining gasification is based on two separate redox processes of a carrier medium, which is called an oxygen carrier. The research on chemical chaining gasification has always been related to oxygen carriers, fuels, and reactors. Oxygen carriers have attracted much attention due to their cost and environmental advantages. Usually, an oxygen carrier is a solid metal oxide that undergoes cyclic reaction and regeneration during the chemical chaining application process. Transition metal oxides are the main raw materials of oxygen carriers. Compared with other metal-based oxygen carriers, iron-based oxygen carriers have received widespread attention due to their good reaction performance, better mechanical properties, wide availability, low price and environmental friendliness. They are the key to the successful operation of chemical chaining gasification technology and the premise and basis for its large-scale application.
[0004] Under high temperature environment, the oxides, chlorides, sulfates and hydroxides produced by biomass decomposition are often gaseous, often adhere to fly ash and oxygen carriers to form slag, reduce the oxygen mobility of iron-based oxygen carriers, and lead to sintering and agglomeration, thereby reducing the chemical activity of oxygen carriers, leading to oxygen carrier deactivation, increasing energy consumption and hidden dangers in the safe operation of equipment. At present, slowing down the deactivation of oxygen carriers and improving reaction performance are urgent problems to be solved in the biomass CLG reaction. Three-dimensional ordered macroporous materials have attracted much attention due to their orderly pore arrangement and large specific surface area, which can improve reaction performance. However, due to the single pore size and large pore size, their mechanical strength is weak and they are prone to agglomeration during high-temperature calcination. Therefore, it is necessary to explore a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size that can significantly slow down the agglomeration phenomenon for biomass chemical chain gasification process, which has a large reaction specific surface area, a developed pore structure and high structural stability. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0006] Another object of the present invention is to provide a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size obtained by the above preparation method.
[0007] Another object of the present invention is to provide an application of the above-mentioned three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0008] The three-dimensional ordered and adjustable aperture iron-aluminum composite metal oxygen carrier obtained by the invention is used in the biomass chemical chain gasification process and can significantly slow down the agglomeration phenomenon.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size comprises the following steps:
[0011] (1) In an inert gas atmosphere, a styrene solution is mixed with an initiator, and then a thermal polymerization reaction is performed under stirring to form polystyrene microspheres, which are then fully stirred for self-assembly and dried to obtain a polystyrene colloidal crystal template;
[0012] (2) Aluminum salt and iron salt are prepared into a precursor solution, and the precursor solution is filled into the gaps of the polystyrene colloidal crystal template by an impregnation method, and calcined to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0013] Preferably, the inert gas in step (1) is at least one of nitrogen, helium and argon; more preferably nitrogen.
[0014] Preferably, the mass concentration of the styrene solution in step (1) is 8-12%; the solvent of the styrene solution is water; more preferably, the mass concentration of the styrene solution is 9%.
[0015] Preferably, the initiator in step (1) is potassium persulfate, and the initiator is added in the form of an initiator aqueous solution, and the concentration of the initiator aqueous solution is 0.50-1.25 mol / L; more preferably, the concentration of the initiator aqueous solution is 1 mol / L.
[0016] Preferably, the molar percentage of the initiator in step (1) to styrene is 4-8%, more preferably 6%.
[0017] Preferably, the stirring speed in step (1) is 200-500 r / min; more preferably, the stirring speed is 200-400 r / min.
[0018] Preferably, the temperature of the thermal polymerization reaction in step (1) is 75-100°C and the time is 12-36 hours; more preferably, the temperature of the thermal polymerization reaction is 80-100°C and the time is 24 hours.
[0019] Preferably, the styrene in step (1) does not contain a polymerization inhibitor, and the method for removing the polymerization inhibitor is: continuously washing the styrene with an alkaline solution with a mass concentration of 3 to 8% to remove the polymerization inhibitor, and fully removing the polymerization inhibitor by reduced pressure distillation at 75 to 90°C.
[0020] Preferably, the drying temperature in step (1) is 60 to 105° C. and the drying time is 12 to 24 hours.
[0021] Preferably, the aluminum salt in step (2) is aluminum nitrate; and the iron salt is iron nitrate.
[0022] Preferably, the molar ratio of the iron salt to the aluminum salt in step (2) is 1:(0.5-3.0); more preferably, the molar ratio of the iron salt to the aluminum salt is 1:1-3; further preferably, the molar ratio of the iron salt to the aluminum salt is 1:2-3.
[0023] Preferably, the concentration of metal cations in the precursor solution of step (2) is 0.5-1.25 mol / L; the solvent of the precursor solution is water; more preferably, the concentration of metal cations in the precursor solution is 1-1.25 mol / L; further preferably, the concentration of metal cations in the precursor solution is 1 mol / L.
[0024] Preferably, in step (2), the mass ratio of the styrene colloidal crystal template to the metal is 1:(0.2-2.5); more preferably, the mass ratio of the styrene colloidal crystal template to the metal is 1:2.
[0025] Preferably, the immersion time in the immersion method of step (2) is 2.5 to 6 hours, more preferably 6 hours.
[0026] Preferably, the calcination in step (2) is calcined at 450-550°C for 6-9h; or first calcined at 450-550°C for 1-3h, and then calcined at 500-900°C for 2-6h; more preferably, the calcination is calcined at 500°C for 6h, or first calcined at 500°C for 2h, and then calcined at 800-900°C for 4h; further preferably, the calcination is first calcined at 500°C for 2h, and then calcined at 800 for 4h.
[0027] Preferably, the calcination in step (2) is carried out in an air atmosphere.
[0028] Preferably, the heating rate of the calcination in step (2) is 2 to 15°C / min; more preferably 10°C / min.
[0029] The preparation method mentioned above obtains a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0030] The above-mentioned three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier is used in chemical chain reforming.
[0031] Preferably, the application is specifically as follows: adding the above-mentioned three-dimensional ordered adjustable pore size iron-aluminum composite metal oxygen carrier into a fuel reactor, first introducing an inert gas to clear the air in the fuel reactor, and then heating the fuel reactor to a reaction temperature. After the temperature of the fuel reactor stabilizes, introducing gas fuel, liquid fuel or solid fuel, and reacting to produce synthesis gas (H2 and CO mixed gas).
[0032] More preferably, the solid fuel is at least one of biomass and organic solid waste fuel; the gas fuel is an alkane fuel; and the liquid fuel is an alcohol or bio-oil fuel.
[0033] More preferably, the flow rate of the inert gas is 90-100 ml / min, and the introduction time (inert gas purge) is 5-10 min.
[0034] More preferably, the molar ratio of the active metal in the three-dimensional ordered adjustable pore size iron-aluminum composite metal oxygen carrier to the carbon in the gas fuel, liquid fuel or solid fuel is 1:(0.2-2.5); more preferably 1:(0.8-2.0).
[0035] More preferably, the reaction temperature is 800-900° C., and the reaction time is 30-45 min.
[0036] More preferably, the biomass is rice husk, which comes from Qilinnan Farm of South China Agricultural University in Guangzhou, China. After washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours and then crushed into particles less than 200 μm using a crusher.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] 1. The present invention adopts an impregnation method to prepare a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size: controllably adjustable single-molecule microspheres are synthesized by emulsion polymerization, self-assembled to form a colloidal crystal template, and a certain proportion of active metals are impregnated to obtain an oxygen carrier with rich and uniform pores, high specific surface area, and adjustable pore size. At the same time, the oxygen carrier has good oxygen transmission capacity and strong anti-agglomeration and agglomeration performance.
[0039] 2. The three-dimensional ordered adjustable pore size iron-aluminum composite metal oxygen carrier material of the present invention can make the pore size of the three-dimensional ordered oxygen carrier adjustable by adjusting the particle size of the microspheres and the degree of stacking of the colloidal crystal template. Aluminum nitrate is added to the three-dimensional ordered iron-based oxygen carrier, and by adjusting Fe / Al, the pores of the three-dimensional ordered macroporous structure are complete, the pore size distribution is concentrated, and the arrangement is neat, thereby improving the specific surface area, oxygen carrying capacity and catalytic properties of the oxygen carrier. It can realize the conversion of pyrolysis liquid phase products into hydrogen-rich synthesis gas under certain reaction conditions. By adjusting the reaction conditions, the ratio of H2 / CO in the synthesis gas can be regulated at about 0.5 to 3.0, which is conducive to preparing synthesis gas according to actual needs.
[0040] 3. The oxygen carrier preparation method of the present invention is prepared by a two-step process. Compared with the existing iron-based oxygen carrier preparation method, it is simple and easy, and has a low cost. Compared with the three-dimensional ordered macroporous oxygen carrier, aluminum nitrate modification is added. Al and Fe in a certain proportion make the pores of the oxygen carrier complete and neatly arranged, and the performance and stability of the oxygen carrier are improved. The pore size is adjustable, the mechanical lightness is high, and it has good oxygen transmission capacity, high reaction activity and anti-agglomeration ability, which is conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The SEM images and particle size calculations of the colloidal crystal templates prepared at different polymerization temperatures in Examples 1 to 2 and Comparative Example 1.
[0042] Figure 2 The SEM images of colloidal crystal templates prepared in Examples 1, 3, 4 and Comparative Example 2 at different stirring rates.
[0043] Figure 3 These are SEM images of oxygen carriers prepared under different calcination temperature conditions in Examples 4, 9, 10 and Comparative Example 3.
[0044] Figure 4 These are SEM images of oxygen carriers prepared under different Fe / Al conditions in Examples 4, 5, 6 and Comparative Examples 4 and 5.
[0045] Figure 5 This is a graph showing the biomass chemical chaining gas selectivity and CH4 conversion rate of oxygen carriers prepared under different calcination temperature conditions in Examples 4, 9, 10 and Comparative Example 3.
[0046] Figure 6 The gasification effect diagram of the oxygen carrier on the biomass chemical chain gasification process under different O / C in Example 4 and the X-ray diffraction diagram of the residue.
[0047] Figure 7 The graph shows the biomass chemical chaining gas selectivity and CH4 conversion rate of oxygen carriers prepared under different precursor solution concentration conditions in Examples 4, 7, 8 and Comparative Examples 6 and 7.
[0048] Figure 8 The graph shows the biomass chemical chaining gas selectivity and CH4 conversion rate of oxygen carriers prepared under different Fe / Al conditions in Examples 4, 5, 6 and Comparative Examples 4 and 5. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0050] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0051] Example 1
[0052] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction under inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain at 200r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template.
[0053] Performance evaluation of gel crystal template:
[0054] The diameter of the styrene microspheres increased to 452nm. After self-assembly, the microspheres were arranged in an orderly manner with a complete structure. The formed colloidal crystal template was uniform and neat, with uniform pore size, large specific surface area and stable structure.
[0055] Example 2
[0056] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 100℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 200r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring for self-assembly, dry the sample at 80℃ for 12h to obtain a polystyrene colloidal crystal template.
[0057] Performance evaluation of gel crystal template:
[0058] The diameter of the styrene microspheres increased to 646 nm. After the microspheres were self-assembled, the ordered structure was relatively complete. The particle size of the formed colloidal crystal template was relatively large, which easily led to an excessively large pore size of the oxygen carrier and a slightly lower mechanical strength.
[0059] Example 3
[0060] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain at 500r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template.
[0061] Performance evaluation of gel crystal template:
[0062] The diameter of the styrene microspheres increases to 860nm. After the microspheres are self-assembled, as the surface area increases, the uniformity of the microsphere particle size decreases, and the uniformity of the formed colloidal crystal template decreases, which easily leads to larger gaps in the oxygen carrier and easy collapse.
[0063] Example 4
[0064] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:2), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template: metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 800℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0065] Evaluation of oxygen carrier reaction characteristics 1:
[0066] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.6 and fully mixed and placed in the center of the quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 29.94%, the gasification efficiency reached 34.99%, and the gas yield reached 0.42Nm 3 / kg.
[0067] Evaluation of oxygen carrier reaction characteristics 2:
[0068] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of a quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 18.50%, the gasification efficiency reached 24.22%, and the gas yield reached 0.26Nm 3 / kg.
[0069] The test results of O / C = 0.2 and 0.4 and other conditions are the same as the above oxygen carrier reaction characteristics evaluation are shown in Figure 6 .
[0070] Example 5
[0071] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:1), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 800℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0072] Evaluation of oxygen carrier reaction characteristics:
[0073] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of a quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 17.32%, the gasification efficiency reached 16.84%, and the gas yield reached 0.21Nm 3 / kg.
[0074] Example 6
[0075] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:3), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 800℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0076] Evaluation of oxygen carrier reaction characteristics:
[0077] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 18.21%, the gasification efficiency reached 22.93%, and the gas yield reached 0.26Nm 3 / kg.
[0078] Example 7
[0079] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as the solvent with a total metal cation concentration of 1.25mol / L (molar ratio of Fe:Al=1:2), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template was placed in an air atmosphere of a muffle furnace and calcined at 500°C for 2h at a heating rate of 10°C / min, and then heated to 800°C for 4h to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0080] Evaluation of oxygen carrier reaction characteristics:
[0081] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of a quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 16.38%, the gasification efficiency reached 14.69%, and the gas yield reached 0.19Nm 3 / kg.
[0082] Example 8
[0083] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as the solvent with a total metal cation concentration of 0.50mol / L (molar ratio of Fe:Al=1:2), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template was placed in an air atmosphere of a muffle furnace and calcined at 500°C for 2h at a heating rate of 10°C / min, and then heated to 800°C for 4h to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0084] Evaluation of oxygen carrier reaction characteristics:
[0085] The biomass chemical chain gasification reaction was carried out on a small fixed bed device. First, the oxygen carrier was ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk was dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200 μm by a grinder) and the oxygen carrier were weighed at O / C = 0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool was plugged at both ends of the oxygen carrier to fix it. Nitrogen was introduced into the quartz tube at a gas flow rate of 100 ml / min and continued to be introduced. When the tubular furnace was heated to 800°C, the quartz tube was placed in the tubular furnace for reaction for 30 minutes. The synthesis gas obtained by the reaction was collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 15.12%, the gasification efficiency reached 13.56%, and the gas yield reached 0.18 Nm 3 / kg.
[0086] Example 9
[0087] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:1), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace in an air atmosphere at a heating rate of 10℃ / min and calcined at 500℃ for 6h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0088] Evaluation of oxygen carrier reaction characteristics:
[0089] The biomass chemical chain gasification reaction was carried out on a small fixed bed device. First, the oxygen carrier was ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk was dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200 μm with a grinder) and the oxygen carrier were weighed at O / C = 0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool was plugged at both ends of the oxygen carrier to fix it. Nitrogen was introduced into the quartz tube at a gas flow rate of 100 ml / min and continued to be introduced. When the tubular furnace was heated to 800°C, the quartz tube was placed in the tubular furnace for reaction for 30 minutes. The synthesis gas obtained by the reaction was collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 17.85%, the gasification efficiency reached 15.66%, and the gas yield reached 0.22 Nm 3 / kg.
[0090] Example 10
[0091] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:2), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 900℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0092] Evaluation of oxygen carrier reaction characteristics:
[0093] The biomass chemical chain gasification reaction was carried out on a small fixed bed device. First, the oxygen carrier was ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilinnan Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk was dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200 μm by a grinder) and the oxygen carrier were weighed at O / C = 0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool was plugged at both ends of the oxygen carrier to fix it. Nitrogen was introduced into the quartz tube at a gas flow rate of 100 ml / min and continued to be introduced. When the tube furnace was heated to 800°C, the quartz tube was placed in the tube furnace for reaction for 30 minutes. The synthesis gas obtained by the reaction was collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 14.93%, the gasification efficiency reached 13.30%, and the gas yield reached 0.17%.
[0094] Comparative Example 1
[0095] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 70°C, and continue to introduce nitrogen into the three-necked flask to keep the reaction under an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 200r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80°C for 12h to obtain a polystyrene colloidal crystal template.
[0096] Performance evaluation of gel crystal template:
[0097] The diameter of the styrene microspheres is 360 nm. After self-assembly, the microspheres have a loose structure and are unevenly arranged. The colloidal crystal template has a loose structure and is easy to collapse.
[0098] Comparative Example 2
[0099] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction under inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain at 600r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template.
[0100] Performance evaluation of gel crystal template:
[0101] The shapes of styrene microspheres are different, and small microspheres are deposited between large microspheres, which interrupts the links between the large microspheres and makes it impossible for the colloidal crystal template to be uniform.
[0102] Comparative Example 3
[0103] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction under inert atmosphere. Then add 50ml 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:2), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace and calcined at 500℃ for 5h to obtain a three-dimensional ordered macroporous iron-aluminum composite metal oxygen carrier.
[0104] Evaluation of oxygen carrier reaction characteristics:
[0105] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of a quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 14.56%, the gasification efficiency reached 14.95%, and the gas yield reached 0.19Nm3 / kg.
[0106] Comparative Example 4
[0107] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=3:1), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 800℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0108] Evaluation of oxygen carrier reaction characteristics:
[0109] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 13.31%, the gasification efficiency reached 15.83%, and the gas yield reached 0.17Nm 3 / kg.
[0110] Comparative Example 5
[0111] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as a solvent with a total metal cation concentration of 1mol / L (molar ratio Fe:Al=1:4), and completely impregnate and fill the inside of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template is placed in a muffle furnace air atmosphere and calcined at 500℃ for 2h at a heating rate of 10℃ / min, and then heated to 800℃ for 4h to obtain a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier.
[0112] Performance evaluation of gel crystal template:
[0113] The diameter of the styrene microspheres becomes larger, the structure of the microspheres becomes loose after self-assembly, the microspheres are unevenly arranged, and they are very easy to sinter and break after calcination.
[0114] Comparative Example 6
[0115] Take 900ml of 9% styrene aqueous solution in a three-necked flask, heat it to 80℃, and continue to introduce nitrogen into the three-necked flask to keep the reaction in an inert atmosphere. Then add 50ml of 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring for self-assembly, the sample was dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as the solvent with a total metal cation concentration of 0.25mol / L (molar ratio of Fe:Al=1:2), and completely impregnate and fill the interior of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry it. The dried colloidal crystal template was placed in an air atmosphere of a muffle furnace and calcined at 500°C for 2h at a heating rate of 10°C / min, and then heated to 800°C for 4h to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0116] Evaluation of oxygen carrier reaction characteristics:
[0117] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of the quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 13.36%, the gasification efficiency reached 12.92%, and the gas yield reached 0.16Nm 3 / kg.
[0118] Comparative Example 7
[0119] Take 900ml of 9% styrene aqueous solution in a three-necked flask and heat it to 80℃, and continue to pass nitrogen into the three-necked flask to keep the reaction under inert atmosphere. Then add 50ml 1mol / L potassium persulfate aqueous solution and maintain it at 400r / min for 24h to fully polymerize styrene to form polystyrene microspheres. After sufficient stirring and self-assembly, the sample is dried at 80℃ for 12h to obtain a polystyrene colloidal crystal template. Prepare a precursor solution containing iron nitrate, aluminum nitrate and water as solvent with a total metal cation concentration of 1.50mol / L (molar ratio of Fe:Al=1:2), and completely impregnate and fill the interior of the above colloidal crystal template (mass ratio template:metal=1:2), let it stand for 6h, and then filter and dry. The dried colloidal crystal template was placed in an air atmosphere of a muffle furnace and calcined at 500°C for 2h at a heating rate of 10°C / min, and then heated to 800°C for 4h to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
[0120] Evaluation of oxygen carrier reaction characteristics:
[0121] The biomass chemical chain gasification reaction is carried out on a small fixed bed device. First, the oxygen carrier is ground and passed through an 80-mesh sieve. Then, the biomass (rice husk, from Qilin South Farm, South China Agricultural University, Guangzhou, China; after washing with ultrapure water, the rice husk is dried in an oven at 105°C for 12 hours, and then crushed into particles less than 200μm by a grinder) and the oxygen carrier are weighed at O / C=0.8 and fully mixed and placed in the center of a quartz tube, and quartz wool is plugged at both ends of the oxygen carrier to fix it. Nitrogen is introduced into the quartz tube at a gas flow rate of 100ml / min and continuously introduced. When the tubular furnace is heated to 800°C, the quartz tube is placed in the tubular furnace for reaction for 30min. The synthesis gas obtained by the reaction is collected by a gas collection bag after cooling and used for gas chromatography to detect the components. After analysis, the carbon conversion rate reached 14.63%, the gasification efficiency reached 12.12%, and the gas yield reached 0.16Nm 3 / kg.
[0122] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier, characterized in that: The following steps are involved: (1) In an inert gas atmosphere, a styrene solution is mixed with an initiator, and then a thermal polymerization reaction is performed under stirring to form polystyrene microspheres, which are then fully stirred for self-assembly and dried to obtain a polystyrene colloidal crystal template; (2) Aluminum salt and iron salt are prepared into a precursor solution, and the precursor solution is filled into the gaps of the polystyrene colloidal crystal template by an impregnation method, and calcined to obtain a three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size.
2. The method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier according to claim 1, characterized in that: The molar ratio of the iron salt to the aluminum salt in step (2) is 1:(0.5-3.0); The concentration of metal cations in the precursor solution of step (2) is 0.5 to 1.25 mol / L; The immersion time in the immersion method of step (2) is 2.5 to 6 hours; In step (2), the mass ratio of the styrene colloidal crystal template to the metal is 1:(0.2-2.5).
3. The method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier according to claim 1, characterized in that: The calcination in step (2) is calcination at 450-550° C. for 6-9 hours; or calcination at 450-550° C. for 1-3 hours, and then calcination at 500-900° C. for 2-6 hours; The calcination in step (2) is carried out in an air atmosphere; The heating rate of the calcination in step (2) is 2 to 15°C / min.
4. The method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier according to claim 1, characterized in that: The mass concentration of the styrene solution in step (1) is 8-12%; The molar ratio of the initiator in step (1) to styrene is 4-8%; The stirring speed in step (1) is 200-500 r / min; The temperature of the thermal polymerization reaction in step (1) is 75 to 100° C. and the time is 12 to 36 hours.
5. The method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier according to claim 1, characterized in that: The temperature of the thermal polymerization reaction in step (1) is 80-100° C.; the stirring speed is 200-400 r / min; The aluminum salt in step (2) is aluminum nitrate; the iron salt is iron nitrate; The molar ratio of the iron salt to the aluminum salt in step (2) is 1:1-3; The concentration of the metal cation in the precursor solution is 1 to 1.25 mol; The calcination in step (2) is calcination at 500°C for 6 hours, or first calcination at 500°C for 2 hours and then calcination at 800-900°C for 4 hours.
6. The method for preparing a three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier according to claim 1, characterized in that: The inert gas in step (1) is at least one of nitrogen, helium and argon; The initiator in step (1) is potassium persulfate, and the initiator is added in the form of an initiator aqueous solution, and the concentration of the initiator aqueous solution is 0.50-1.25 mol / L.
7. A three-dimensional ordered iron-aluminum composite metal oxygen carrier with adjustable pore size obtained by the preparation method according to any one of claims 1 to 6.
8. Application of the three-dimensional ordered and adjustable pore size iron-aluminum composite metal oxygen carrier as claimed in claim 7 in chemical chain reforming.
9. The use according to claim 8, characterized in that: The application is specifically as follows: adding the three-dimensional ordered adjustable pore size iron-aluminum composite metal oxygen carrier as described in claim 7 into a fuel reactor, first introducing an inert gas to clear the air in the fuel reactor, then heating the fuel reactor to a reaction temperature, and after the temperature of the fuel reactor stabilizes, introducing gas fuel, liquid fuel or solid fuel to react and produce synthesis gas.
10. The use according to claim 9, characterized in that: The solid fuel is at least one of biomass and organic solid waste fuel; the gas fuel is an alkane fuel; the liquid fuel is an alcohol or bio-oil fuel; The molar ratio of the active metal in the three-dimensional ordered adjustable pore size iron-aluminum composite metal oxygen carrier to the carbon in the gas fuel, liquid fuel or solid fuel is 1: (0.2-2.5); The reaction temperature is 800-900° C., and the reaction time is 30-45 minutes.